1989
DOI: 10.1002/jat.2550090510
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of dietary cadmium on heart and kidney antioxidant enzymes: Evidence for the greater vulnerability of the heart to cadmium toxicity

Abstract: This study demonstrates the greater susceptibility of the heart as compared to the kidney to cadmium in the presence of high dietary selenium. Male weanling rats were fed an adequate-copper low-selenium feed supplemented with 0, 10 or 50 ppm copper with or without 50 ppm dietary cadmium for 7 weeks. All rats received 0.5 ppm selenium in their drinking water. Cadmium treatment resulted in histopathological lesions in the heart, but not in the kidney. Although cadmium treatment resulted in more extensive effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 33 publications
2
16
0
2
Order By: Relevance
“…Studies carried out in vivo designed to elucidate the role of peroxidation in cadmium cardiotoxicity have demonstrated that GSH-Px is more important than either SOD or catalase in preventing Cdinduced peroxidation (Jamall & Smith, 1985a;Jamall & Sprowls, 1987). A central role for GSH-Px in preventing tissue peroxidation is also supported by studies carried out in vitro (Jones et al, 1981;Jones & Kennedy, 1983;Suttorp et al, 1986;Raes et al, 1987).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Studies carried out in vivo designed to elucidate the role of peroxidation in cadmium cardiotoxicity have demonstrated that GSH-Px is more important than either SOD or catalase in preventing Cdinduced peroxidation (Jamall & Smith, 1985a;Jamall & Sprowls, 1987). A central role for GSH-Px in preventing tissue peroxidation is also supported by studies carried out in vitro (Jones et al, 1981;Jones & Kennedy, 1983;Suttorp et al, 1986;Raes et al, 1987).…”
Section: Introductionmentioning
confidence: 62%
“…A treatment period of 8 weeks was selected because earlier studies in our laboratory have established that feeding weanling rats a low-Se diet for this length of time.results in a depletion of GSH-Px to less than 10 % with peroxidative tissue injury (Jamall & Smith, 1985a;Jamall & Sprowls, 1987). In addition, dietary 3-AT treatment allowed us to study the effects of a sustained reduction of hepatic catalase activity.…”
Section: Necropsy and Tissue Homogenizationmentioning
confidence: 99%
“…Cadmium accumulates in the body because of slow excretion. Cd causes toxicity in different organs, heart is one of the most effected tissues and oxidative damage usually occurs after Cd toxicity (1)(2)(3)(4). Many mechanisms are defined to explain pathophysiology of the Cd toxicity; inflammation is one of them (5).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of toxic metals in cardiac oxidative damage suggests that this organ shows a great vulnerability to metal intoxication [9][10][11][12]. Notwithstanding, and despite the magnitude of the knowledge so far accumulated, the biochemical basis for the observed in vivo oxidative effects of vanadium in cardiac tissue are still poorly defined.…”
Section: Introductionmentioning
confidence: 99%